2021
DOI: 10.3390/ijms22031033
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Complex Interplay of Transcription Factors Orchestrating Seed Oil Content in Brassica napus L.

Abstract: Transcription factors (TFs) and their complex interplay are essential for directing specific genetic programs, such as responses to environmental stresses, tissue development, or cell differentiation by regulating gene expression. Knowledge regarding TF–TF cooperations could be promising in gaining insight into the developmental switches between the cultivars of Brassica napus L., namely Zhongshuang11 (ZS11), a double-low accession with high-oil- content, and Zhongyou821 (ZY821), a double-high accession with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…In the same way, NAC genes were upregulated after the induction of a cold shock [47]. Interestingly, we have shown that members of TF families such as GATA, DOF, NAC, or MYB are important regulators of genes with a monotonic expression pattern in both cultivars in the seed tissue by forming TF co-operations [48].…”
Section: Transcription Factor Binding Site Enrichment Analysismentioning
confidence: 69%
“…In the same way, NAC genes were upregulated after the induction of a cold shock [47]. Interestingly, we have shown that members of TF families such as GATA, DOF, NAC, or MYB are important regulators of genes with a monotonic expression pattern in both cultivars in the seed tissue by forming TF co-operations [48].…”
Section: Transcription Factor Binding Site Enrichment Analysismentioning
confidence: 69%
“…Thus, large changes in the gene expression patterns associated with glycolysis can probably also affect the allocation of carbon between different storage compounds during the development of seeds. However, there is a complex interplay between different transcription factors involved in seed developmental processes that can also be of importance for metabolic switches directed to oil synthesis ( Fatihi et al, 2016 ; Rajavel et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two distinct sets of ME-lncRNAs (with corresponding p-values) were found with ascending or descending monotonic expression patterns. To meet the efficient level of stringency for monotonicity, we defined the parameters as permut = 100, svdetimes = 100, and svdenoise = 0.1, according to (Rajavel et al, 2021). Eventually, ME-lncRNAs with a CPM >1 and sample variance for discriminating error value ≤1 were considered as significant ME-lncRNAs.…”
Section: Identification Of Monotonically Expressed Lncrnasmentioning
confidence: 99%